Evaluasi dan Pengembangan Sistem Akuntansi pada Koperasi Konsumen “KSM” Sehat Sejahtera Kota Metro - Era Yudistira; Esty Apridasari; Nur Aini (Pusat Riset dan Inovasi Nasional, 2025)
The rapid development of Micro Small Medium Enterprises (MSMEs) indicates that they play a significant role in the national economy. One of the growing MSMEs in Metro City is “KSM Sehat Sejahtera” whose operational activities focus on the production and sale of fertilizer to farmers. The current growth in fertilizer sales by KSM is quite good and has even expanded beyond Lampung. However, this development has not been accompanied by the availability of an adequate accounting system because the lack of accounting knowledge and weaknesses in the use of the accounting system. The approach used in this community service activity is Service Learning (SL). Service Learning is a combination of academic materials and community service activities. The output of this activity is the understanding and development of accounting systems in businesses in the production sector, specifically at KSM Sehat Sejahtera, to make a cooperative accounting system design and financial reports. The community service activity is carried out in four stages. The first stage is interviews and observations with the cooperative to obtain information related to the current business profile and condition. The second stage is evaluation and discussion based on the information obtained from the first stage. The third stage is training for KSM regarding accounting systems and financial reporting. Then, the fourth stage is assistance in developing an accounting system at KSM Sehat Sejahtera by creating an accounting system design such as profit and loss report and a financial position report.